(untitled)
This paper attempts to describe and explain the phonological process of assimilation in Bisaya, an indigenous language spoken in Saba h. The current description is couched in the frameworks of autosegmental phonology (Goldsmith, 1990) and geometry features of Halle-Sagey model (Halle, 1992). The assimilation processes described here are stop nasalisation and vowel harmony. Stop nasalisation is a process where oral stops become nasal stops, and vowel harmony is a process whereby vowels within words are required to share one or more phonological properties. The process of assimilation is analyzed in this study as spreading of an autosegment that maps certain features from the source segment to the target segment, which finally leads to phonological modification. Stop nasalisation involves the spreading of[+ nasal